Discourses of rivalry or rivalry of discourses: discursive strategies and framing of Chinese and Japanese foreign policies in Central Asia. Issue 1 (2nd January 2020) - Dadabaev, Timur
Abstract: This article analyzes discursive strategies of China and Japan to integrate newly emerging Central Asian (CA) states into their internal and external policies, norms and concepts, according to which they justify both their actions in CA and CA responses to these policies. This article elaborates the concept that to a certain extent, the interests of China and Japan in CA are similarly focused on mineral resources and political stability. However, these countries employ different discursive strategies to frame their approaches and goals. This article also emphasizes that the discourse of competition for regional domination prevalent in the English language, Russian and some CA media is largely an imposition of a zero-sum vision of international relations that is not proven by any empirical evidence. On the contrary, many of the projects conducted both by China and Japan are compatible – if not supplementary – and do not necessarily imply exclusivity of interest. At the same time, both China and Japan have different ways of reasoning their CA engagements, resulting in a rivalry of discourses for the 'hearts and minds' of the CA population.